Radiographic study on relation of the periapical status and frequency of endodontic treatment of teeth with and without apical periodontitis in an Iraqi population . (Mustansiria Dental Journal, 2019)
Aim: The point of the study was to assess the prevalence of apical periodontitis andfrequency of endodontic treatment in an Iraqi population.Materials and methods: Panoramic radiographs of 300 Iraqi subjects 18-60 yearsold. The periapical status of all teeth (with the exception of third molars) wasexamined using periapical index scoring system (PAI). Information wereinvestigated statistically using the Chi-squared test at the significance level ofp